The native south : new histories and enduring legacies - Garrison, Tim Alan, 1961-; O'Brien, Greg, 1966- (University of Nebraska Press, 2017)
Tim Alan Garrison and Greg O'Brien assemble contributions from leading ethnohistorians of the American South in a state-of-the-field volume of Native American history from the sixteenth to the twenty-first century. Spanning such subjects as Seminole-African American kinship systems, Cherokee notions of guilt and innocence in evolving tribal jurisprudence, Indian captives and American empire, and second-wave feminist activism among Cherokee women in the 1970s, the book offers a dynamic examination of ethnohistorical methodology and evolving research subjects in southern Native American history. Theda Perdue and Michael Green, pioneers in the modern historiography of the Native South who developed it into a major field of scholarly inquiry today, speak in interviews with the editors about how that field evolved in the late twentieth century after the foundational work of James Mooney, John Swanton, Angie Debo, and Charles Hudson.